The Short Shrift? Policy Implications for Low-Scoring African American - Amy Pickard (Adult Education Research Conference, 2014)
This paper presents findings from a critical analysis of Pennsylvania adult literacy policy and program participation rates by race and educational functioning level to address the question of the provision of equitable educational services to African American participants assessed as reading at a 5th grade level equivalent and below.